Review of Empirical Research on Transformational Leadership and Organizational Performance of Local Government - Siswadhi, Ferry; Widyastuti, Tri; Sawitri, Ni Nyoman; Afrianti, Fitrina (Yayasan Sinergi Kawula Muda, 2024)
This review aims to present a systematic review of empirical research on transformational leadership (TL) and local government performance (LGP) to synthesize the fragmented knowledge and propose a unifying framework for future research. This research adopts a systematic literature review methodology. A total of 22 articles were reviewed after being filtered from 59 articles found through an exhaustive search of online databases: Scopus, Emerald Insight, Science Direct, JSTOR, Taylor and Francis, and Google Scholar. Inclusion criteria were peer-reviewed empirical studies published in English from 2012 to 2024. Exclusion criteria were articles that did not provide empirical results on the relationship between TL and LGP and were published older than 2012. A matrix table was developed to extract and organize information from the articles. The findings revealed three main vital themes. First, general organizational performance is the background most studied in the TL-LGP. Second, almost all studies use quantitative methods to analyze the data collected. Third, in general, the empirical results reported the influence of TL on LGP. A lot of background context still needs to be studied, and qualitative and mixed-method methods will be challenging for future research.